The anatomy of Chinese innovation: Insights on patent quality and ownership - Philipp Boeing; Loren Brandt; Ruochen Dai; Kevin Lim; Bettina Peters (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
We study the evolution of patenting in China from 1985-2019. We use a Large Language Model to measure patent importance based on patent abstracts and classify patent ownership using a comprehensive business registry. We highlight four insights. First, average patent importance declined from 2000-2010 but has increased more recently. Second, private Chinese firms account for most of patenting growth whereas overseas patentees have played a diminishing role. Third, patentees have greatly reduced their dependence on foreign knowledge. Finally, Chinese and foreign patenting have become more similar in technological composition, but differences persist within technology classes as revealed by abstract similarities.
Keywords: O30; 330; China; innovation; patents; large language model